Volume 10 Number 3 2014
DOI: 10.18057/ijasc.2014.10.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Compression Behavior of Doubler-Plate Reinforced Square Hollow Section T-Joints

Abstract: ABSTRACT:The doubler-plate is widely used to improve the behavior of truss joints, and it has been proven to be effective in increasing the load carrying capacity of circle or square hollow section joints, yet the current design approach for doubler-plate reinforced joints is elementary. This study investigates the behavior of doubler-plate reinforced square hollow section (DPR-SHS) T-joints under brace compression, by experimental tests and finite element analysis (FEA). Details of the test arrangement were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…However, further parametric studies also observed the failure of chord web buckling, especially for CPR SHS joints with a high β and τ2 ratio [19,20] . This is mainly due to the "over-reinforcement" effect of the collar plate for the chord flange, which has also been observed for DPR SHS T-joints [21,22] . Although both the above failure modes have been observed for CPR SHS joints under compressive load, their identification criteria is not yet clear, which brings uncertainties for the prediction of the joint strength.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…However, further parametric studies also observed the failure of chord web buckling, especially for CPR SHS joints with a high β and τ2 ratio [19,20] . This is mainly due to the "over-reinforcement" effect of the collar plate for the chord flange, which has also been observed for DPR SHS T-joints [21,22] . Although both the above failure modes have been observed for CPR SHS joints under compressive load, their identification criteria is not yet clear, which brings uncertainties for the prediction of the joint strength.…”
Section: Introductionmentioning
confidence: 70%
“…To eliminate the effects of chord material properties and dimension, the normalized load-deformation curves are commonly used [2,4,21] , by which two dimensionless parameters are employed, as shown by Eq. (4) and Eq.…”
Section: Table 4 Parametric Matrix For Cpr Shs T-jointsmentioning
confidence: 99%
See 3 more Smart Citations